Exploring the Parents’ Disciplinary Strategies to Promote Children’s Learning Interest - Hambala, Kwenberlin; Lopez, Enid Chloe; Cobrado, Dhianne; Naparan, Genesis; Dela Pena, Geraldine; Tantog, Alfer Jann (Papanda Publisher, 2023)
Discipline and interest are aspects of parenting that affect children’s behavior and academic performance. This study explores the parents’ disciplinary strategies to promote children’s learning interests. The researchers conducted this study due to society’s issue and observation that elementary pupils have a low interest in learning and manifested inappropriate behaviors inside and outside the classroom. The participants were the ten selected parents with children enrolled in 5th Grade in one of the private Catholic elementary schools in Pagadian City, Philippines. A single case study was utilized. It was found that parents experienced challenges in disciplining their children to promote learning interests due to different kinds of behaviors that the children manifest. The participants identified the following behaviors: Too Much Screen Time in Playing Mobile Games and Being Disrespectful. Despite the challenges they have encountered, they were able to overcome those by implementing positive discipline, offering the problem to God, and effective communication to build good relationships with their children. It is important to be gentle and firm in implementing discipline to promote the learning interest of the pupils. Positive discipline inside the classroom allows the pupils to develop skills of responsibility, resiliency, and proper behavior with the use of positive and negative reinforcements that will motivate them to be interested in learning and excel academically.